Factors influencing managerial challenges for smallholder and emerging sheep and goat farmers in the Thabo Mofutsanyana District, Free State Province, South Africa - Neriath, Kgomongwe; Leonah, Mthombeni, Danisile; Akwasi, Antwi, Michael (Asian Journal of Agriculture and Rural Development, 2024)
This study aimed to identify and analyse the determinants of managerial challenges for smallholder and emerging sheep and goat farmers in the study area by highlighting key factors in order to create an enabling environment for the farmers to improve production and income. A stratified random sampling technique was used to select 145 participants from a pull sampling frame of 251 participants. A semi-structured questionnaire was used to collect the data by interviewing 145 selected smallholder farmers. The Statistical Package for Social Science (SPSS), version 28.0, was used to analyse the data. Descriptive statistics and the probit regression model were used to analyse the determinants of the managerial challenges for smallholder and emerging sheep and goat farmers. The results of the study show that only 19% of the participants had business plans, and the absence of business plans impacted farm and livestock management negatively. The probit results indicated that the age of the respondents, off-farm activities, and access to market information had a positive and significant association with managerial challenges. It is recommended that youth and women be encouraged to engage in sheep and goat farming for better management and that farmers must focus their attention on livestock farming instead of off-farm income-generating activities. The Department of Agriculture and municipalities should initiate extension programs that focus on farm and livestock management as well as access to market information.